Ecosystem Services and Cash Crop Tradeoffs of Summer Cover Crops in Northern Region Organic Vegetable Rotations - Wauters, Vivian M.; Grossman, Julie M.; Pfeiffer, Anne; Cala, Rodrigo (Frontiers in Sustainable Food Systems, 2021)
Intensive production practices characterizing vegetable farming contribute to high productivity, but often at the expense of supporting and regulating ecosystem services. Diversification with cover crops may support increased resilience through soil organic matter (SOM) contributions and physical soil protection. Vegetable farming often includes spring and fall production, limiting establishment and productive potential of over-wintered cover crops that are more widely used in the USA. In northern climate vegetable systems, warm-season cover crops planted during short summer fallows could be a tool to build resilience via ecosystem service enhancement. This project evaluated summer cover crops in the northern USA (MN and WI) for biomass accumulation, weed suppression, and contribution to fall cash crop yield. Our study included four site years, during which we investigated the effects of four cover crop species treatments, grown for 30 (short duration, SD) or 50 days (long duration, LD) alongside bare fertilized and unfertilized control treatments: buckwheat (Fagopyrum esculentum) and sunn hemp (Crotalaria juncea) monocultures, and biculture of chickling vetch (Lathyrus sativus) or cowpea (Vigna unguiculata) with sorghum-sudangrass (sudex) (Sorghum bicolor x S. bicolor var. Sudanese). To quantify cover crop quantity, quality, and weed suppression capacity, we measured cover crop and weed biomass, and biomass C:N. To quantify effects on cash crops, we measured fall broccoli yield and biomass. Mean total biomass (cover crop + weeds) by site year ranged from 1,890 kg ha−1 in MN Y1 to 5,793 kg ha−1 in WI Y2 and varied among species in Y1 for both the SD and LD treatments. Most cover crops did not outcompete weeds, but treatments with less weeds produced more overall biomass. Data from Y1 show that cover crops were unable to replace fertilizer for fall broccoli yield, and led to reduced fall crop yield. Broccoli in Y2 did not reach maturity due to fall freeze. Summer cover crops, because of their biomass accumulation potential, may be used by farmers in northern climates to fit into cropping system niches that have historically been left as bare soil, but care with timing is necessary to optimize weed suppression and mitigate tradeoffs for cash crop production.